Revisiting the Zinc-Blende/Wurtzite Heterocrystalline Structure in CdS. (9th June 2014) - Zhou, Zhaohui; Li, Mingtao; Wu, Po; Guo, Liejin
Abstract : The band offset at CdS zinc-blende (ZB)/wurtzite (WZ) heterocrystalline interface was revisited using the first principles calculations with the local density approximation (LDA), generalized gradient approximation (GGA), and Heyd-Scuseria-Ernzerhof (HSE06) hybrid functional. It was revealed that, unlike most IV, III-V, and II-VI semiconductors, the band alignment at CdS ZB/WZ heterocrystalline interface was of type-I with straddling lineup of band edges, which was irrespective of the exchange-correlation energy functional, the thickness of ZB and WZ segments, and the ZB/WZ interface location. The partial charge densities of VBM and CBM states were separated around two adjacent interfaces in one unit cell of heterocrystalline superlattice. This type of carrier localization was mainly attributed to the spontaneous polarization occurring in the WZ segment rather than the band offset at the interface.